Estudo da desidratação de tomates em pedaços com pré-tratamento osmótico - Souza, Josilma Silva de (2002)
Vegetables drying plays an important role in the field of food dehydration, being a very old practice that was originated from sun drying items of food in order to preserve them to be consumed during the periods of scarcity. One of these vegetables is the tomato, that was originally grown in South America. Tomatoes are easily perishable after being picked up from the tree and this makes the process of tomato dehydration a challenge due to the high amount of water (95%) contained in them. The present research work was mainly intended to develop alternative processes for tomato conservation, by drying slices of skinned and unskinned tomatoes in the in natura form or in the osmotically pre-dehydrated form. Firstly, the best conditions of the osmotic pre-dehydration process were defined including temperature, immersion time and concentration of the osmotic solution, based on the results of water loss, solids gain and weigh reduction of the pre-dehydration tomatoes at different processing conditions. The osmotic solution used was made up of NaCl (5 and 10%) and sucrose (25 and 35%) at different combinations. For a fixed conditions of osmotic pre-dehydration, the drying tests of the pre-processed and in natura tomatoes were carried out in a stove with air circulation and a convective dryer with trays, at two levels of temperature. The sensorial analysis of the osmotically pre-treated and unskinned dehydrated tomatoes was carried out as well as a study on the their shelf-live. The results obtained showed that the drying of the tomatoes took place as a result of the internal control of the water transport, and did not show a constant rate, while two distinct periods of the decreasing phase were observed. The osmotic pre treatment substancially reduced the initial amount of humidity in the tomatoes, thus reducing the necessary time for the product to attain levels of intermediate humidity. The impermeability of the tomato skin was identified as well as the unfavorable influence of the pre-treatment on the unskinned tomatoes, whose solid gain brought about a decrease in the water activity with subsequent reduction of the drying rate. Despite the various simplifications carried out during the development of this study, the proposed diffusive model adjusted to the experimental data satisfactorily, thus making it possible to determine the effective coefficients of diffusion, whose results were consistent and compatible with those found in the current literature. Concerning the higher rates of evaporation and the lowest processing time, the best results were obtained in the drying of the unskinned, in natura tomatoes and of the skinned, pre-dehydrated tomatoes, at 60ºC, both processed in the convective drier. The results of the sensorial analysis of the unskinned and pre-treated product did not prove to be satisfactory. Regarding the shelf-live of the tomatoes, for a period of 45 days, no physicochemical or microbiological alteration of the product was noted